ANALYSIS OF THE AERODYNAMIC EFFECT OF FUSELAGE INTERACTION ON THE PUSHER PROPELLER PERFORMANCE ON UAV ALAP-ALAP BPPT - Suprianto, Agus
In this study, the authors examined with experiment laboratory the effect of the aerodynamic interaction frontal area of the UAV Alap-Alap BPPT model on the performance of the propeller configured with the pusher type, and in addition testing was carried out using only a test equipment without fuselage. In the process of making test specimens, fuselage is made using acetal thermopalstic material with a 3D printer machine printing method, while carbon fiber propellers are made by lamination method, namely extraction from original propeller geometry and then made positive molds to produce new products. Furthermore, the experimental results were compared with numerical computational fluid (CFD) simulation approaches. The results of the two methods are obtained namely the graph value of thrust coefficient (CT), power (CP), and efficiency (?) between propeller performance with or without fuselage, for cases where the interaction of aircraft fuselage placed in front of the propeller tends to give a lowering effect CT and CP at the same advance ratio point to the value generated from the nonfuselage configuration, so that the peak propeller efficiency value us with the fuselage configuration decreases by about 5% at the same position of advance ratio (J) from the unconfigured propeller efficiency value without fuselage. Validation of the CFD simulation results provides a comparison of the trend value of the graph which is almost the same as the experimental results. Meanwhile after CFD model validated, the value of lift (L) and drag (D) force of fuselage model can show from post processing result with increase trend value.